Improvement of zinc bioleaching from a zinc flotation concentrate using mechanical activation. (15th March 2021) - Zahiri, Ali; Ahmadi, Ali; Foroutan, Abdolrahim; Ghadiri, Mahdi
Highlights: Mechanical activation accelerated the bioleaching of zinc sulfide concentrate. Pyrite addition had a significant effect on the zinc bioleaching of the concentrate. Mechanical activation increased the anodic oxidation of the zinc concentrate. Abstract: The effects of mechanical activation and pyrite addition on the bacterial and electrochemical aspects of the zinc bioleaching from a sulphide concentrate was evaluated. The experiments were performed in the presence of a mixed culture of moderately thermophilic microorganisms in shake flasks and a stirred tank reactor. Electrochemical analyses were performed to find the process mechanisms. Mechanical activation increased zinc bioleaching from 49% and 61.4% to 62.5% and 72.2% in the presence of 0 and 30 wt% pyrite addition, respectively. The reason for the enhancement of zinc bioleaching for the mechanically activated samples was the increasing of contact area of target minerals and change in the mineral structure. Furthermore, the electrochemical analysis results confirmed that the mechanical activation was significantly increased the rate of sphalerite anodic oxidization.